2018
DOI: 10.1016/j.ygeno.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Functional network analysis reveals biological roles of lncRNAs and mRNAs in MOG35–55 specific CD4+T helper cells

Abstract: Long non-coding RNAs have the potential to regulate immune responses. Their impact on multiple sclerosis has remained elusive. For illustrating their roles in experimental autoimmune encephalomyelitis (EAE) pathogenesis, we investigated the differential expression of lncRNAs and mRNAs in CD4Th cells obtained from myelin oligodendrocytic glycoprotein(MOG)-induced EAE and complete Freund's adjuvant (CFA) controls. We observed differential expression of 1112 lncRNAs and 519 mRNAs in CD4Th cells. The functional ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Though the study was unable to identify differential expression of either the lncRNA candidate or its associated gene, significant correlation between lnc-IL-7R and IL-7Ra were seen in both MS and healthy groups. These studies suggest a potential functional role of lncRNA transcripts in regulation of gene targets in MS. Several studies using animal models have also considered the role of lncRNAs in MS pathogenesis (Duan et al, 2018;Guo et al, 2017;Li et al, 2018;Liu et al, 2018;Sun et al, 2017), or combinations of human participants and animal model studies (Masoumi et al, 2019;Pahlevan Kakhki et al, 2018). These studies have demonstrated the role of multiple lncRNA transcripts in differentiation of CD4 + T cell linages.…”
Section: Introductionmentioning
confidence: 99%
“…Though the study was unable to identify differential expression of either the lncRNA candidate or its associated gene, significant correlation between lnc-IL-7R and IL-7Ra were seen in both MS and healthy groups. These studies suggest a potential functional role of lncRNA transcripts in regulation of gene targets in MS. Several studies using animal models have also considered the role of lncRNAs in MS pathogenesis (Duan et al, 2018;Guo et al, 2017;Li et al, 2018;Liu et al, 2018;Sun et al, 2017), or combinations of human participants and animal model studies (Masoumi et al, 2019;Pahlevan Kakhki et al, 2018). These studies have demonstrated the role of multiple lncRNA transcripts in differentiation of CD4 + T cell linages.…”
Section: Introductionmentioning
confidence: 99%